2012
DOI: 10.1002/jcu.22013
|View full text |Cite
|
Sign up to set email alerts
|

The yield of EUS‐FNA in undiagnosed upper abdominal adenopathy is very high

Abstract: EUS-FNA allows for excellent tissue acquisition in abdominal lymphadenopathy. Our study supports the use of traditional EUS imaging criteria to identify suspected malignant adenopathy. The results from our large cohort of patients show that EUS-FNA should be considered as a first-line diagnostic modality for ascertaining the etiology of abdominal lymphadenopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…In three retrospective studies, totalizing 476 patients with mediastinal or upper abdominal LN of unknown origin, adequate specimens were reported in 87-100% of cases and accuracy for correct diagnosis in 85-98%. [424344] Prevalence of malignant disease was between 37% and 50% with a large variability for the lymphoma proportion in these series (8-46%).…”
Section: Performance Of Eus-fna According Type Of Pathologymentioning
confidence: 84%
“…In three retrospective studies, totalizing 476 patients with mediastinal or upper abdominal LN of unknown origin, adequate specimens were reported in 87-100% of cases and accuracy for correct diagnosis in 85-98%. [424344] Prevalence of malignant disease was between 37% and 50% with a large variability for the lymphoma proportion in these series (8-46%).…”
Section: Performance Of Eus-fna According Type Of Pathologymentioning
confidence: 84%
“…Histologically, pancreatic cystic lymphangiomas consist of interconnecting cysts separated by septa, lined by epithelial cells, and contain serous, serosanguineous, or chylous fluid. 127 EUS imaging of pancreatic cystic lymphangiomas can be similar to mucinous lesions of the pancreas, but the diagnosis of pancreatic cystic lymphangioma is made if the aspirated fluid is chylous in appearance and has an elevated triglyceride level. If the fluid aspirated is serous and only has a mildly elevated triglyceride level, then it may be difficult to differentiate from other pancreatic cystic neoplasms.…”
Section: Other Rare Cystic Neoplasmsmentioning
confidence: 99%
“…Bohle et al reported a diagnostic accuracy of 92% for mediastinal and intra‐abdominal lymphadenopathy with EUS‐FNA. In another study, Coe et al reported an overall diagnostic accuracy of 87% for undiagnosed intra‐abdominal lymphadenopathy. For pancreatic lesions, two recent meta‐analyses reported a pooled accuracy of 85–92% .…”
Section: Discussionmentioning
confidence: 96%